Data authorisation and validation in autonomous vehicles: a critical review - Reem Alhabib; Poonam Yadav (Discover Applied Sciences)
Abstract Autonomous Vehicles (AVs) are becoming increasingly prevalent due to their potential to improve road safety and reduce environmental impact. These vehicles rely on Automated Driving Systems (ADS), which integrate multiple sensors and actuators. While some AVs operate with minimal human intervention, fully autonomous systems eliminate the need for human control entirely. Despite advances in AV technologies, secure and trustworthy data management remains a significant challenge. This survey focuses on two relatively underexplored aspects in AV environments: data authorisation and validation. It examines the key related challenges and reviews existing solutions. The findings highlight critical gaps in current approaches and suggest future research directions to enhance AV data authorisation and validation.